Optimalisasi Pengelolaan Media Sosial Melalui Pelatihan Citizent Journalist untuk Mempromosikan Branding Kampung Wisata Literasi Pekijing - Adin Maqbadudin,; Bangun Yoga Wibowo,; Evi Afiati, (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service aims to improve the ability of teenagers in Kampung Wisata Literasi Pekijing to manage social media through a citizen journaslit training program. The main issue is that social media is not being used effectively as a tool for promotion and branding the village. The method used is the Asset-Based Community Development (ABCD) approach, which includes interactive lectures, discussions, and hands-on practice. Evalution was done using pre-test and post test through the Quizizz platform. The results show an improvement in teenagers’ understanding of social media management, as seen in the higher post-test scorers compared to the pre-test. Additionally, this activity also changed how the teenagers see social media, shifting their view from just a source of entertainment to a tool for sharing information and promoting the literary tourism village.